Incidence of Fever Associated With Dexmedetomidine in the Adult Intensive Care Unit. (October 2022) - Peterson, Jacob; Thomas, Wendy; Michaud, Christopher; Parker, Jessi
Background: Published literature has described the temporal relationship of dexmedetomidine with elevated temperatures, but there is limited data to quantify the incidence of fever in ICU patients receiving dexmedetomidine. Objective: The primary objective of this study was to estimate the incidence of temperature greater than or equal to 38.5°C in ICU patients receiving dexmedetomidine. Methods: This was a retrospective cohort study of ICU patients who received dexmedetomidine with a propensity-matched subgroup analysis comparing dexmedetomidine fever patients to non-fever patients. Patients 18 years of age and older admitted between November 2017 and August 2018 who received continuous dexmedetomidine for 6 or more hours were eligible for inclusion. Included patients with a temperature of great than or equal to 38.5°C while receiving dexmedetomidine were established as having dexmedetomidine-related fever. Results: Of 882 eligible ICU patients, 404 dexmedetomidine patients were included in the study. Sixty-one patients (15.1%) met the definition for the primary endpoint. Forty-two patients who received dexmedetomidine but experienced no fever were matched for multivariate analysis. The fever group received a higher mean maximum infusion rate (0.98 µg/kg/h ± 0.43 vs. 0.68 µg/kg/h ± 0.42, P < 0.001) and a longer median duration of dexmedetomidine (43.0 hours [range 7-711] vs. 24.3 hours [6-148], P = 0.001) compared to the non-fever group. Conclusion: Fever greater than 38.5°C was observed in 15.1% of ICU patients while receiving dexmedetomidine. Prospective studies are warranted to validate these findings.